International experience in measuring digital transformation and lessons for Vietnam - Le Thi Hoai Thu; Nguyen Quynh Mai (Journal of State Management, 2025)
The strong digitalization process is driving organizations to transform in order to adapt and develop. Accurately identifying the level of digital transformation enables managers to formulate effective policies, optimize resource allocation, and comprehensively promote the transformation process. This article analyzes and synthesizes international experiences in measuring digital transformation from organizations and countries around the world, drawing lessons for Vietnam. By reviewing various measurement models, the article clarifies the trend toward developing integrated and multi-dimensional indicator systems that reflect both effectiveness and readiness for digital transformation at national and organizational levels. At the same time, the article also evaluates the current measurement models in Vietnam and proposes directions for improvement to enhance accuracy, comprehensiveness, and practical relevance.